Assessing the knowledge, attitude, and practice of hepatitis B virus infection in allied health workers in Johannesburg - Mokoka-Nkhobo, Ledile (My University, 2018)
Background Hepatitis B virus is a common viral disease with a high global prevalence and associated high mortality rates. The virus is transmitted by parenteral mucosal exposure to HBsAg–positive body fluids from persons who have acute or chronic HBV infection. The increase in communicable diseases worldwide has necessitated the need for adequate knowledge on the prevention and transmission of these diseases by medical personnel. The focus of this study is the knowledge, attitude and practice of Hepatitis B virus (HBV) infection, which is an easily transmittable blood-borne pathogen that poses an immense threat to health personnel occupational hazard. Even though Hepatitis B Virus infection is preventable, many healthcare workers may remain ignorant of its risks and may not practice adequate preventive measures. Objectives To assess the knowledge, attitude and practice of Allied health care workers on the prevention of hepatitis B virus infections at three academic teaching hospitals of the University of the Witwatersrand, namely Charlotte Maxeke Johannesburg Academic Hospital (CMJAH), Helen Joseph Hospital (HJH), and Chris Hani Baragwanath Hospital (CHBH). Methods A cross-sectional descriptive study was conducted on allied healthcare workers from the three academic teaching hospitals using a questionnaire to collect demographic information; knowledge, attitude and practice about Hepatitis B virus infection. The data was quantitatively analysed using Stata statistical package and Likert Scales to code the participants’ responses. Results Of the 260 healthcare workers surveyed, 220 returned their completed questionnaires (85% response rate). The majority of the respondents were female (77%). The respondents included 23% Physio/ OT, 18% Technicians/technologists, 6% Speech therapists, 5% radiographers while 45% had other occupations. More than half of the workers (59%) were between 22 and 30 years old, 30% were 13 – 45 years old, 10% were older than 45 years old while 1% of the sample did not indicate their age. Almost all workers, (97.2%) indicated that they had knowledge about hepatitis B infection. There was no difference in this opinion by gender (p-value = 0.612). The workers got to know about hepatitis mainly from formal teaching in their training (73.5%), 16% from workshop training at work and 15.1% from media. The source of information did not differ significantly by gender as all the p-values were non-significant. The results showed that there is no association between occupation and gender (p-value = 0.754) since the p-value was greater than 0.05. There was also no association between several years employed since the chi-square p-value was greater than 0.05 (p-value = 0.820). There was a significant relationship between knowledge on complications of hepatitis B infection by occupation with 84% of the other workers indicating that one of the complications is cirrhosis with other occupations having lower percentages mentioning cirrhosis and 79% of the same group of workers having the highest mention of liver cancer. The p-values for cirrhosis (.001) and liver cancer (0.000) were less than 0.05. The unvaccinated participants held low positive attitudes, with a median, mode and mean score of 1 (likely score from +4 to -4). Most of the respondents (79%) practised the right compliance with common precautions, and most of the participants (64.9%) were vaccinated. Overall respondents showed substantially superior knowledge (p< 0.001), safer practices and positive attitudes (p=0.001). Conclusions Hepatitis B infection is well known amongst allied health workers at the three South African hospitals, but there is reluctance towards HBV preventative measures hence it is a high risk. It is recommended that efforts should be made to increase the vaccination coverage and accessibility of the HBV vaccine at the hospitals. It is necessary to increase awareness campaign and training of AHCW on HBV transmission and preventive measures.
A research report submitted to the University of the Witwatersrand in partial fulfilment of the requirements of the degree of Master of Medicine 2018